Growth and Yield Performance of F1-Hybrid Sweet Corn (Zea mays saccharata) under Soil Drenching and Foliar Spray of Eco-Enzyme - Novisrayani Kesmayanti; Ummi Kalsum; Edi Romza; Ruli Joko Purwanto; Widya Irmawati; Yani Purwanti (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Sweet corn is a horticultural crop with high economic value and steadily increasing market demand. However, sweet corn productivity in Indonesia remains relatively low, ranging from 8 to 10 tons per hectare, well below its genetic potential of 12 to 15 tons per hectare. This low productivity is attributed to several factors, including soil fertility degradation caused by unsustainable cultivation practices, pest and disease infestations, and limited farmer access to quality agricultural inputs at affordable prices. Sweet corn plants respond well to inorganic fertilizers; however, long-term use of these fertilizers can degrade soil quality and fertility, reduce microbial activity, and increase production costs. Moreover, excessive reliance on inorganic fertilizers leads to soil nutrient imbalances, reduced organic matter content, and adverse environmental impacts. Therefore, efforts are needed to reduce this dependence, one of which involves utilizing eco-enzymes as an organic nutrient supplement. This study aimed to evaluate the growth and yield responses of Hybrid-F1 sweet corn plants to reduced NPK fertilizer doses, combined with eco-enzyme application via soil drenching and foliar spray. The study employed a Randomized Block Design with four replications and four treatment levels, comparing full NPK fertilizer doses, a 50% reduction in NPK fertilizer combined with eco-enzyme, and standalone eco-enzyme application. The results demonstrated significant improvements in fertilization efficiency, with the combination of a 50% reduction in NPK fertilizer and weekly applications of 1 ml/l eco-enzyme via soil drenching and foliar spray achieving optimal growth and production equivalent to full fertilization. Another important finding is that eco-enzyme can be used independently without inorganic fertilizers; plants still grew normally and produced ears, although yields were relatively lower. For best results, it is recommended to use a combination of a 50% reduction in NPK fertilizer dose and eco-enzyme application through both soil drenching and foliar spray. This approach not only reduces production costs by up to 50% but also promotes more sustainable and environmentally friendly cultivation practices.